Dravet syndrome: Early electroclinical findings and long‐term outcome in adolescents and adults. (6th January 2020) - Darra, Francesca; Battaglia, Domenica; Dravet, Charlotte; Patrini, Mara; Offredi, Francesca; Chieffo, Daniela; Piazza, Elena; Fontana, Elena; Olivieri, Giorgia; Turrini, Ida; Dalla Bernardina, Bernardo; Granata, Tiziana; et al.
Abstract: To describe the outcome of Dravet syndrome (DS) in adolescents and adults we conducted a longitudinal retrospective study of two independent cohorts of 34 adolescents (group 1) and 50 adults (group 2). In both cohorts, we collected information about genetic mutation, and semiology of seizures at onset and during disease course. At the last evaluation, we considered the following features: epilepsy (distinguishing myoclonic/complete and nonmyoclonic/incomplete phenotype), neurologic signs, intellectual disability (ID), and behavioral disorders. Moreover, in both cohorts, we performed a correlation analysis between early characteristics of the disease and the outcome of DS with regard to seizure persistence, ID, behavioral disorder, and neurologic impairment at last evaluation. Group 1 includes 22 adolescents with complete form of DS and 12 with incomplete form; group 2 includes 35 adults with complete form and 15 with incomplete form. The seizures persisted in 73.6% of adolescents and in 80% of adults, but epilepsy severity progressively decreased through age. Seizure persistence correlated with the complete phenotype and with the occurrence of reflex seizures. At last evaluation, ID was moderate or severe in 70.5% of adolescents and in 80% of adults. The most severe cognitive and motor impairment was observed in patients with persisting seizures. The severity of cognition, language, and neurologic impairment at last evaluation correlated statistically with the complete phenotype. The study confirms that the global outcome of DS is poor in most cases, albeit epilepsy severity decreases throughout adulthood. The improvement of epilepsy throughout ages is not associated with improvement in intellectual abilities and motor skills; this confirms that the unfavorable outcome is not a pure consequence of epilepsy.